Bimbingan Perkawinan terhadap Pembentukan Keluarga Sakinah (Studi Kasus di KUA Sumberjambe, Kabupaten Jember) - Awaliya Safithri; Ahmad Ryan Sugianto; Achmad Chumaidi Ubaidillah Azhar (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
ABSTRACT This study aims to analyze the contribution of marriage guidance to the formation of sakinah families in KUA Sumberjambe, Jember Regency. This guidance is seen as a preventive and promotive step in preparing the bride-to-be to live a harmonious home life based on Islamic values. This study uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with religious extension workers, guidance participants, and direct observation of the guidance process. Marriage guidance at KUA Sumberjambe plays a strategic role in realizing a sakinah family based on sharia maqashid. This program not only instills religious values (hifz al-din), but also protects the soul (hifz al-nafs), intellect (hifz al-'aql), heredity (hifz al-nasl), property (hifz al-mal), and safeguards human dignity (karamah al-insan). Through comprehensive materials and an interactive approach, the bride-to-be is equipped with an understanding of sharia, communication skills, conflict management, and financial planning. This guidance is also promotive and preventive, encouraging the creation of benefits while preventing harm such as divorce and domestic violence. Post-marriage counseling strengthens the implementation of these values in real life. Thus, marriage guidance at KUA is not just an administrative procedure, but an effective instrument in building a harmonious, stable, and blessed family in accordance with Islamic principles and the goals of sharia. Keywords: Contribution, Marriage Guidance, Sakinah Family, KUA Sumberjambe.